An analytical approach for inorganic selenium speciation in tap water samples: HPLC - continuous flow hydride generation - FAAS - Tutar, Bahar Karademir; Tutar, Omer Faruk; Bodur, Suleyman; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
Inorganic selenium speciation is a crucial topic since selenite (Se(IV)) and selenate (Se(VI)) have different toxicity and bioavailability. Therefore, a high performance liquid chromatography-continuous flow hydride generation (containing an online pre-reduction process)-flame atomic absorption spectrometry (HPLC-CFHGFAAS) was proposed to carry out inorganic selenium speciation in tap water samples. Parameters of HPLC and CFHG systems were comprehensively optimized to obtain sufficient peak resolution and high signal to noise ratio. After, analytical figures of merit of the HPLC-CFHG-FAAS system for Se(IV) and Se(VI) were examined. Limit of detection (LOD)/limit of quantitation (LOQ) for Se(IV) and Se(VI) were recorded as 0.09/0.31 mg/kg (as Se) and 0.23/0.77 mg/kg (as Se), respectively. Acceptable recovery results were calculated in the range of 72.0 %-101.5 % and 104.0 %-115.9 % via matrix matching calibration (MMC) strategy for Se (IV) and Se(VI), respectively. The obtained recovery results presented that the proposed method can be applied for the speciation of inorganic selenium in tap water samples.
Keywords: FAAS; Hydride generation; Inorganic selenium speciation; Online pre-reduction using thiourea/HCl; mixture; ATOMIC-ABSORPTION-SPECTROMETRY; PERFORMANCE LIQUID-CHROMATOGRAPHY; EMISSION-SPECTROMETRY; UV-IRRADIATION; PRE-REDUCTION; FOOD SAMPLES; ICP-OES; INJECTION; SE(VI); PRECONCENTRATION; Chemistry; Food Science & Technology